2021
DOI: 10.1039/d1qi00145k
|View full text |Cite
|
Sign up to set email alerts
|

Two C2v symmetry dysprosium(iii) single-molecule magnets with effective energy barriers over 600 K

Abstract: Two mononuclear DyIII single-molecule magnets (SMMs) with C2v coordination symmetry were synthesized. Both of them have strong uniaxial magnetic anisotropy with high effective energy barriers for magnetization reversal over 600...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 54 publications
0
16
0
Order By: Relevance
“…A new method proposed by Aravena et al 31 to predict effective demagnetization barrier based on the same CASSCF/RASSI-SO calculations was also used for comparison. The theoretically predicted effective barrier as a function of temperature has the form: 31–34 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A new method proposed by Aravena et al 31 to predict effective demagnetization barrier based on the same CASSCF/RASSI-SO calculations was also used for comparison. The theoretically predicted effective barrier as a function of temperature has the form: 31–34 …”
Section: Resultsmentioning
confidence: 99%
“…S5,† the M in the ground KDs are all smaller than 10 −5 μ B , and thus the QTMs in their ground KDs could be suppressed at low temperatures. 6,32 Table S8† lists wave functions with definite projection of the total moment | m J > for the lowest two or three KDs with different θ angles, where the ground KDs with θ ranging from 36.3° to 54.3° are all mostly composed by m J = ±15/2.…”
Section: Resultsmentioning
confidence: 99%
“…11 The intrinsic high spin of many lanthanide ions and their strong spin-orbit coupling make them attractive candidates for assembling single-molecule magnets. [12][13][14][15][16][17][18][19][20][21] Another aspect of interest in lanthanide complexes is molecular refrigeration which can be generated by the so-called magnetocaloric effect (MCE). It has been shown that the MCE can be maximized by the presence of metal ions that can contribute to a high spin and have negligible anisotropy.…”
Section: Introductionmentioning
confidence: 99%
“…During the periods of pursuing high-performance SMMs and obtaining the magneto–structural correlations, we have studied the influence of magnetic exchange interactions on improving the blocking temperature in radical-bridged systems, the influence of guest solvent exchange in the pores of a metal–organic framework on the magnetization dynamics of Dy 2 -SMM nodes, , as well as the influence of terminal halogen ligands on the SMM behaviors . The key of these studies is to keep the main coordination structures unchanged but vary one specific structural factor, which is highly challenging in synthetic coordination chemistry.…”
Section: Introductionmentioning
confidence: 99%